Self-informant Agreement for Personality and Evaluative Person Descriptors: Comparing Methods for Creating Informant Measures - Simms, Leonard J. (2010)
Little attention typically is paid to the way self-report measures are translated for use in self-informant agreement studies. We studied two possible methods for creating informant measures: (a) the traditional method in which self-report items were translated from the first- to the third-person and (b) an alternative meta-perceptual method in which informants were directed to rate their perception of the targets’ self-perception. We hypothesized that the latter method would yield stronger self-informant agreement for evaluative personality dimensions measured by indirect item markers. We studied these methods in a sample of 303 undergraduate friendship dyads. Results revealed mean-level differences between methods, similar self-informant agreement across methods, stronger agreement for Big Five dimensions than for evaluative dimensions, and incremental validity for meta-perceptual informant rating methods. Limited power reduced the interpretability of several sparse acquaintanceship effects. We conclude that traditional informant methods are appropriate for most personality traits, but meta-perceptual methods may be more appropriate when personality questionnaire items reflect indirect indicators of the trait being measured, which is particularly likely for evaluative traits.